Effect of some parameters on the separation process of a saboted bullet - Bui, Xuan Son; Nguyen, Quang Tuan; Nguyen, Hai Minh (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: In this paper, the influence of muzzle velocity and the initial friction between the sabot and the penetrator of a sub-caliber bullet on the separation process was investigated. A special armor-piercing bullet was chosen as a research object. Methods: A hybrid approach was applied in the study to solve the set tasks. In the first place, the equation system describing the motion of the sabot and the penetrator was established analytically. The aerodynamic drags acting on the sabot and the penetrator were then obtained numerically using CFD methods. Eventually, the equations of motion of the sabot and the penetrator were solved using the Runge-Kutta method to analyze the effect of the bullet muzzle velocity and the initial friction of the sabot and the penetrator on the separation process.Results: The research results have shown the significant influence of the bullet muzzle velocity and the initial friction on the parameters of the sabot and the penetrator at the very moment they completely separate from each other. Based on the obtained data, weapon designers can appropriately select the ballistic and structural parameters for the bullet.Conclusion: The hybrid approach presented in this paper is effective in studying the separation process of armor-piercing saboted bullets. The research results are useful contributions to the field of sub-caliber ammunition. The presented method can be applied in the design process of armor-piercing saboted projectiles of different calibers.
Keywords: sabot separation; sub-caliber bullets; Ansys Fluent; CFD; numerical simulation